Relatório técnico sobre roda de conversa online: Parentalidade no autismo - rodas de conversa online - Andrade, Julyana Lima Vasconcelos (2022)
Autism Spectrum Disorder (ASD) is considered a neurodevelopmental disorder by the Diagnostic and Statistical Manual of Mental Disorders (DSM-V). Facing an autistic condition of a child, the parents may feel a disruption of ideals. Until the diagnosis investigation process begin, the parents go through certain looks and says from relatives and friends, in addition to some notes from school about the peculiarities of their child's behavior. During this time, questions arise, along with helplessness and failure feelings that summon us to think about the extent of care directed towards an autistic child or in severe psychological distress as well as in the gear of the production of scientific knowledge that the syntagma of autism reveals to us. This context demands us to think about symptoms, diagnosis and responsibility of autistic family members who experience conflicts in the midst of COVID-19 pandemic, where social isolation becomes an express recommendation of World Health Organization (WHO), having as a direct consequence the disruption in old ways of living, putting everyone in an unprecedented life experience, in addition to new challenges. Therefore, our production consists of a conclusive technical advisory report regarding online conversation circles proposed independently that were later incorporated into the extension actions of Água de Chocalho project, associated to the Laboratório de Clínica, Sujeito e Políticas Públicas (CLIPSUS) [Laboratory of Clinic, Subject and Public Policy], from Universidade Federal do Ceará – Campus Sobral [Federal University of Ceará] and from the Mestrado Profissional em Psicologia e Políticas Públicas [Professional Master in Psychology and Public Policy]. In total, we had 189 direct beneficiaries (family members, children and autistic subjects that were interested in participating in the circle) and 756 indirect beneficiaries as the community that surrounds these subjects. Our data collection happened from June 2020 to June 2021, counting 25 conversation circles. For analysis and discussions of the collected data, we used Bardin's content analysis (2016), considering the qualitative nature of the search. As a result, we were able to build three categories of analysis: “COVID-19 pandemic and the impacts on the life of children and family members of autistic subjects”; “motherhood, family and autism” and “school experience of autistic subjects and public policy”. This work is guided by ethical, clinical, theoretical and methodological assumptions of psychoanalysis. Therefore, adopting these assumptions, the knowledge resulting from the experience would appear après-coup, a posteriori, a proper time of elaboration on the unconscious. Thus, it is essential to build and maintain welcoming and dialogical spaces for autistic family members, understanding the power that these encounters have. In order to build policies in sync with the reality of these countless families, specially mothers, that experience the care of a so-called autistic subject with almost no support, we must welcome family members so they can take part in the inclusion strategies and therapeutic planning.